Analysis of Financial Risk Disclosure in State-Owned Enterprises in the Infrastructure Sector - Annisa Rahmawati; Isna Putri Rahmawati (AKUMULASI: Indonesian Journal of Applied Accounting and Finance, 2024)
This study aims to determine financial risk disclosure, liquidity risk disclosure, credit risk disclosure, interest rate risk disclosure, exchange rate risk disclosure, capital structure risk disclosure, and general risk disclosure. This research is qualitative descriptive research that describes financial risk disclosure in detail. The object of this research is the infrastructure sector State-Owned Enterprises listed on the Indonesia Stock Exchange from 2021 to 2023, totaling six companies. The data analysis method is done by content analysis. The results show that the overall level of financial risk disclosure increases from 2021 to 2022 but remains the same in 2023. The same level of risk disclosure for three years occurs in the disclosure of liquidity risk, interest rate risk, exchange rate risk, and general risk. Credit risk disclosure increases from 2021 to 2023, while capital structure risk disclosure decreases in 2023.